The Role of Industrial Design in the Sustainable Mobility of D. M. Quito - Remache, Abel (2021)
This article analyzes the mobily sustainability, their characteristics, their relationship with industrial design, advantages and key points of focus for the design of this in the City of Quito, especially the Metro mobility project. With the characteristics of the Smart City, the development of society is sought by establishing an environmental, social and economic balance and uses technology as an ally to sustain its development by analyzing the different transport projects implemented in the most developed cities, presenting itself as the biggest problem that is going through, and for this industrial design arises as a response to build an intelligent city focused on improving decision making, the efficiency of operations and innovation processes, the provision of urban products and services and their competitiveness thanks to its ability to understand technological, social and environmental processes from a systemic perspective, in which relationships are the basis of its action, providing clear and profitable solutions to transform current cities into Smart Cities. The Quito metro is currently the most important project within the area of   mobility of the city, which imposes a new milestone towards prosperity in the development of smart cities in Latin America, providing a facility to mobilize in means of transportation, reduction of vehicular traffic, greater reception of foreigners and their own and achieving the contentment and comfort of its residents and citizens in this new era.